Effect of temperature on life cycle and behaviour of Aedes aegypti (Diptera: Culicidae) (Bangladesh Journal of Zoology, 2022)
In this study, effect of increasing temperature on life cycle, mortality, and behavior of the mosquito species, Aedes aegypti was evaluated. Heat shock was applied at 32°C, 37°C and 42°C for 20 minutes, 1 hour and 2 hours for each temperature to egg, 2nd instar, 3rd instar and pupal stage separately and changes in life cycle pattern was recorded on a routine basis. The control temperature was 27°C at which the mosquito was reared. When heat-shock was applied to eggs, the developmental period for each stage was found to be inversely proportional to temperature rise. The shortest embryonic developmental period was recorded at 32°C, and the shortest larval and pupal stages were recorded at 37°C (2h). The shortest full development period was also found to be at 37°C (2h). No hatching was recorded at 42°C. While heat shock was applied to 2nd instar larvae, 3rd instar larvae and pupae, similar decreased pattern was observed. In this study, 100% viability was observed upon heat shock to eggs, larvae (2nd and 3rd instar) and pupae at 27°C and 32°C. In case of 37°C, egg, 2nd instar and pupal viability decreased. No egg hatched at 42°C, while few 2nd instars survived. Lowest viability rate for 3rd instar larvae and pupae were counted at 42°C. Change in the rate of movement also decreased gradually with increasing temperatures in pupae. The change was irregular in case of 2nd and 3rd instar larvae. The highest movement was recorded for 2nd and 3rd instar larvae at 32°C and 27°C, respectively and lowest was recorded at 42°C.Bangladesh J. Zool. 49 (3): 369-379, 2021